SEJARAH DAN PERKEMBANGAN OBOE SERTA IMPLEMENTASINYA TERHADAP TEKNIK PERMAINAN - imal yakin (LPPMPP Institut Seni Indonesia Padangpanjang, 2011)
Oboe instrument first time created by Jean Hotteterre and Michel Philidor in the year 1660, and first time used in writing in music partitur in the year 1671 in activity opera